2013
DOI: 10.4103/0970-0358.121995
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different positions on lower limbs skin perfusion pressure

Abstract: We have encountered situations of patients with critical limb ischemia accompanied by pain at rest and necrosis, who hang their legs down from the bed during sleep. This lower limb position is known to be a natural position, which reduces pain in the lower extremity induced by ischemia. However, the effect of this position on blood flow of the lower extremity is poorly understood. We studied whether measurements of skin perfusion pressure (SPP) changes by leg position and the difference between healthy adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
(11 reference statements)
1
13
0
2
Order By: Relevance
“…Kawasaki et al found that the circulation of lower limbs is better in hanged positions (in a lower level than heart), but staying for a long time in this position causes venous congestion, edema and delayed wound healing (11). Our study indicated that 30-degree elevation of upper limb could reduce the interstitium fluid and edema.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Kawasaki et al found that the circulation of lower limbs is better in hanged positions (in a lower level than heart), but staying for a long time in this position causes venous congestion, edema and delayed wound healing (11). Our study indicated that 30-degree elevation of upper limb could reduce the interstitium fluid and edema.…”
Section: Discussionsupporting
confidence: 47%
“…They concluded that in sitting position and appropriate leg position, skin perfusion pressure was increased significantly compared with other positions in both healthy adults and critical patients. These results suggest that sitting position is effective to keep an appropriate blood stream of lower limbs not only in healthy adults but also in patients with critical limb ischemia (11). Therefore, it seems that limb elevation could be effective to prevent and reduce limb edema.…”
Section: Introductionmentioning
confidence: 78%
“…[14]. They found that SPP was increased significantly in sitting position in both critical limb ischemia and healthy control groups [14]. In Figure 2, we discovered that HbO2 and HbT concentrations were changed in a similar trend between three groups at each stage of Buerger's exercises.…”
Section: Discussionmentioning
confidence: 81%
“…The amount of HbT (The sum of HbO2anddeoxy-Hb) in a given area of tissue could indirectly represent the blood flow of the peripheral tissue in our unique apparatus. [14]. They found that SPP was increased significantly in sitting position in both critical limb ischemia and healthy control groups [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation